A produção de leite como estratégia de desenvolvimento para o Rio Grande do Sul - Benedito Silva Neto (Desenvolvimento em Questão, 2005)
The paper discusses the role that the milk production can carry out in a development strategy for the Rio Grande do Sul State (Brazil). It was verified that an important contribution that the milk production could provide to the development it derives of its capacity of maintenance of the population in the rural zones, which enhance its effects on the local economies. These effects are generated by the high potential of aggregation of value that the dairy activity can provide in a direct, indirect and induced way. So for the milk production can play this function, however, it is necessary orientate the current policies sustained by the representatives of the agro-industrial chain that can lead more than two thirds of the producers to the exclusion in the short period. The main conclusion of the paper is that the promotion of production systems adapted to the conditions of the family production would be an indispensable condition for the construction of a development model more equitable and balanced territorially